Analisis Implementasi Hidden Curriculum dalam Pembentukan Karakter Siswa di SMA Pondok Schooling Darul Ilmi Kabupaten Bandung (Kajian Berbasis Analisis SWOT) - Kika Nawang Wulan; Sedarmayanti Sedarmayanti; Yuyun Yuniarsih; Kosasih Kosasih (Universitas Negeri Malang, 2020)
Abstract: This study aims to analyze the implementation of the hidden curriculum in shaping students’ character at SMA Pondok Schooling Darul Ilmi in Bandung Regency and to formulate strategic strengthening based on SWOT analysis. The research employed a qualitative approach with a phenomenological design to explore students’ lived experiences and the process of value internalization within the daily life of a boarding school environment. Data were collected through in-depth interviews, limited participant observation, and document analysis. The primary research subjects were students selected purposively to represent everyday experiences in the boarding school setting, while supporting informants included the principal, teachers, homeroom teachers, dormitory mentors, and school staff who interact closely with students. Data credibility was ensured through source and technique triangulation as well as interview verification through member checking. Data analysis was conducted thematically through the stages of data reduction, data display, and conclusion drawing. The findings were further interpreted through a managerial perspective using the POLC functions (planning, organizing, leadership, and controlling) and were strategically mapped using a Qualitative Integrated SWOT framework. The results indicate that students’ character development primarily occurs through structured habituation embedded in the daily rhythm of classroom and dormitory life, the role modeling of adult actors within the school, the quality of teacher–student relationships, and the application of educational and restorative consequences. The dominant character values identified include integrity, discipline, responsibility, empathy, and emotional regulation. The boarding school environment functions as a social ecosystem that strengthens value internalization through repeated social interaction, collective norms, and consistent institutional culture. SWOT analysis reveals that the effectiveness of the hidden curriculum is supported by the structured boarding school rhythm and strong relational culture, although it still requires reinforcement through consistent role modeling, improved restorative consequences, and strengthened digital literacy and student self-regulation. Keywords: hidden curriculum; character education; boarding school; educational management; SWOT analysis. Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi hidden curriculum dalam pembentukan karakter siswa di SMA Pondok Schooling Darul Ilmi Kabupaten Bandung serta merumuskan strategi penguatan berbasis analisis SWOT. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologis untuk memahami pengalaman dan proses internalisasi nilai yang dialami peserta didik dalam kehidupan keseharian di lingkungan sekolah berasrama. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif terbatas, dan studi dokumentasi. Subjek utama penelitian adalah peserta didik yang dipilih secara purposif sebagai representasi pengalaman hidup di sekolah pondok, sementara informan pendukung meliputi kepala sekolah, guru, wali kelas, pamong, dan staf sekolah yang berinteraksi intensif dengan siswa. Keabsahan data dijaga melalui triangulasi sumber dan teknik serta verifikasi hasil wawancara (member checking). Analisis data dilakukan secara tematik dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan, kemudian diperkaya melalui pembacaan manajerial fungsi POLC (planning, organizing, leadership, controlling) serta pemetaan strategis menggunakan pendekatan Qualitative Integrated SWOT. Hasil penelitian menunjukkan bahwa pembentukan karakter siswa terutama berlangsung melalui mekanisme pembiasaan yang terstruktur dalam ritme kehidupan kelas dan asrama, keteladanan aktor sekolah, kualitas relasi antara guru dan siswa, serta desain konsekuensi yang bersifat edukatif dan restoratif. Nilai karakter yang paling menonjol meliputi integritas, disiplin, tanggung jawab, empati, dan pengendalian emosi. Lingkungan sekolah pondok berfungsi sebagai ekosistem sosial yang memperkuat internalisasi nilai melalui interaksi sosial yang berulang, norma kolektif, dan budaya institusional yang konsisten. Analisis SWOT menunjukkan bahwa keberhasilan implementasi hidden curriculum didukung oleh ritme kehidupan berasrama dan budaya relasional yang kuat, namun tetap memerlukan penguatan melalui konsolidasi keteladanan, desain konsekuensi yang lebih edukatif, serta penguatan literasi digital dan kontrol diri siswa. Kata kunci: hidden curriculum; pendidikan karakter; sekolah berasrama; manajemen pendidikan; analisis SWOT